A natureza de um território no sertão do norte de Minas Gerais : a ação territoriar dos Xakriabá - Silva, Cássio Alexandre da (2014)
The research project entitled The nature of a territory in the sertão of Minas Gerais north area: The action territoriar of the Xakriabá , is the conclusion of a PhD in Planning Area Management, a concentration area from the Geography Institute s Graduation Program from the Federal University of Uberlândia UFU. In the movement process between empiric and theory, we proposed to study the territory. The purpose of this research permeates two important issues. The first covers the multidimensional study of the territory and the second encompasses the relationship between the territory and the community in the constant struggle and resistance around the expansion to the São Francisco River, within the space time dimension. The thesis that we constructed and defend is that the Xakriabá people do multidimensional territorial actions, characterized as territoriar action which is the act of socio-spatially organize itself at the banks of the São Francisco River, in the north countryside of Minas Gerais since the eighteenth century. The overall goal is to analytically understand the Xakriabá territory from its multidimensionality as well as its territorial constitution in spatial-temporal processes. In order to do so, it is important to identify the extent of the practices and social relations; to understand, through the dimension of representations and language, the discourse analysis about the territory in a geographical perspective; to analyze the historical dimension; and to map the recognized territories . The territory presents in its constitution several territorialities of material and symbolic nature. The justification is revealed by the study and multidimensional analysis concerning the territory category, as well as elements of recognition and social, economic, political, environmental, cultural, geographical and historical representations in the ancestral territory of the Xakriabá people in the banks of the São Francisco River. The basic methodology consists of fieldwork as a participant researcher, photographic records, semi-structured interviews, document comparisons, mapping territories and especially the analysis of discourse. The recognition of ancestral territory constitutes the ransom of cultural representations, as well as the relations between knowledge and practice. This paper seeks to contribute to other analyses of indigenous relations in the construction of its territory, territoriality and the actions territoriar etno-geographically.